The emerging role of Mule and ARF in the regulation of base excision repair. - Khoronenkova, S; Dianov, G (2011)
The ARF (Alternative Reading Frame) protein is encoded in the Ink4a locus of human chromosome 9 that is frequently mutated in cancer cells. It was recently demonstrated that ARF is induced in response to DNA damage and inhibits, by direct interaction, the E3 ubiquitin ligase Mule that regulates p53 protein levels. Mule inhibition leads to p53 accumulation and activates cellular DNA damage responses. Mule has also recently been identified as a major E3 ubiquitin ligase involved in the regulation of DNA base excision repair. In this review, we will summarise the major properties of Mule and ARF and their roles in the coordination of DNA repair and DNA replication.